2020
DOI: 10.1016/j.omtn.2020.09.011
|View full text |Cite
|
Sign up to set email alerts
|

circFLT1 and lncCCPG1 Sponges miR-93 to Regulate the Proliferation and Differentiation of Adipocytes by Promoting lncSLC30A9 Expression

Abstract: Although many circular RNAs (circRNAs) and long non-coding RNAs (lncRNAs) have been discovered in adipocytes, their precise functions and molecular mechanisms remain poorly understood. Based on existing circRNA and lncRNA sequencing data of bovine adipocytes, we screened for the differential expression of circFLT1 and lncCCPG1 in preadipocytes and adipocytes and further analyzed their function and regulation during adipogenesis. The overexpression of ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…have identified that six circRNAs play potential functions during yak adipocyte differentiation. Kang et al [ 88 ] have discovered that circFLT1 and lncCCPG1 are differentially expressed in bovine adipocytes. Overexpression of circFLT1 and lncCCPG1 together promotes adipocyte differentiation and inhibits adipocyte proliferation.…”
Section: Circrnas Related To Adipocyte Metabolismmentioning
confidence: 99%
“…have identified that six circRNAs play potential functions during yak adipocyte differentiation. Kang et al [ 88 ] have discovered that circFLT1 and lncCCPG1 are differentially expressed in bovine adipocytes. Overexpression of circFLT1 and lncCCPG1 together promotes adipocyte differentiation and inhibits adipocyte proliferation.…”
Section: Circrnas Related To Adipocyte Metabolismmentioning
confidence: 99%
“…The 179/192-bp DNA sequence containing the 13-bp region was cloned into psiCHECK-2 using T4 DNA Ligase and the insert was released by XhoI and NotI digestion (TaKaRa Biotech Co., Ltd.). The miR-181 sequence was cloned into the pcDNA3.1 vector (Invitrogen) as described previously (Kang et al, 2020;Hao et al, 2021), and the insert was released by KpnI and XhoI digestion.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…CircINSR could target miR-15/16 to inhibit the pre-mature differentiation of intramuscular preadipocytes [ 15 ]. CircFLT1 and lncCCPG1 sponges miR-93 to regulate the proliferation and differentiation of adipocytes in bovine [ 16 ]. These discoveries demonstrate the importance of lncRNAs and circRNAs in adipogenesis.…”
Section: Introductionmentioning
confidence: 99%